The Dialectic of Antagonism Between What Seems To Be Disparate More Often Than Not (Poetry and Science) : A Study of Selected Illustrative Poems by Monica Ong - Haraj , Hassan Abdul Ameer; Haraj, Sahar Abdul Ameer (International Journal of Psychosocial Rehabilitation, 2020)
Through science represented by shapes of the medical-emotional scenery of personal displacement, Monica Ong explores the cultural silences that outspreading from China to the Philippines as well as North America. Poetry in this sense has been fed by science through using image-poems compared to diagram and diary. Such scientific diagrams represent witness to diminished histories of the body. Ong by doing so, she discharges silence through the lack of language as well as historical eliminator , the loss of cultural retention, restored truths, as well as ghosted personalities. Ong tries to inquire the social hierarchies as well as gender roles of her rearing. Thus by employing certain medical images and drawings like x-rays scans, anatomical drawings to make the poem similar to a visual journey in memory and culture to decide our identities.Ong through a usage of a visual art as well as poetry which in other words similar to the collaboration between science and poetry into a hybrid form evolves a new way of reading the poem. So what seems to be odd apparently has a connection in a far more deeper level. Consequently her aim was to say that the body is not just a biological body but a way of narration, a narrator that can narrate much in an expressive way.